A Study on Incidence and Patterns of Acute Poisoning Cases in an Emergency Department of Western Region of Nepal - Acharya, K.; Kandel, I.S.; Gupta, S.; Poudel, S.D. (Journal of Gandaki Medical College-Nepal, 2019)
Introduction: Poisoning is a common cause of morbidity and mortality in the Nepal. The objective of our study is to evaluate the incidence and pattern of acute poisoning cases admitted to the Gandaki Medical Teaching Hospital. Methods: This is cross-sectional observational study carried out among acute poisoning cases attending emergency department from January 2015 to December 2017. Results: A total of 156 poisoning cases were treated of which female patients were 71% and the highest numbers (36.5%) of patients were in the age group 21 to 30 years. Organophosphates poisoning was the commonest poison diagnosed among 28.8%, followed by rodenticide poisoning found among 27.5%. Psychiatric illnesses were present among 94.8% of our patients. The most common diagnosis were Anxiety and depression 46.6% followed by family dispute among 30.4%. Above fifty percent of our patients attended our emergency department within 2 hours our ingestion of poisons. Conclusion: Female and young people are at greater risk of acute poisoning. Pesticides were the most common agent. The reasons for the poisoning need to be carefully evaluated and proper support and advice must be given in poisoning cases.